Pengaruh Pengaruh Literasi Konsep Halal, Religiusitas, dan Sikap Konsumen Terhadap Keputusan Penggunaan Halal Fashion: Studi Kasus Mahasiswa/I Bogor - Dinda Kartika Mawarda Putri; Nurizal Ismail (Masyarakat Ekonomi Syariah Bogor, 2025)
Indonesia is the country with the second largest Muslim population in the world, reaching 241.7 million people. With this large population, the domestic market potential for halal products is very promising. According to data from the State of the Global Islamic Report (SGIER) 2023/2024, the amount of halal product consumption in the world is estimated to reach USD 2.4 trillion in 2024. This places Indonesia in a strategic position to become one of the world's halal product production and distribution centers. Indonesia has succeeded in occupying the 3rd position globally for the modest fashion industry. The Ministry of Industry (Kemenperin) estimates that the halal industry in Indonesia will increase by 14.96% or US 281.6 billion in 2025. Where, halal fashion is an important part of the halal industry itself. And has the potential to become one of the main pillars supporting the national economy in the future. This study aims to test the influence of halal concept literacy, religiosity, and consumer attitudes on the decision to use halal fashion products in Bogor. This study uses quantitative methods and sampling techniques using purposive sampling. The research instrument was a structured questionnaire with a Likert scale of 1-6. The basis of this study used Partial Least Square-Structural Equation Modeling (PLS-SEM) with the help of Smart-PLS 3.0 software on 105 respondents. This article's research shows that halal literacy has a negative and insignificant effect on the decision to use halal-labeled fashion products. Religiosity has a positive and significant effect on the decision to use halal fashion. Consumer attitudes also have a positive and significant effect on the decision to use halal-labeled fashion. Keywords: Halal literacy, Religiosity, Consumers, Decision to Use, Fashion, Smart-PLS